2010
DOI: 10.1111/j.1365-2265.2010.03877.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of paediatric hyperthyroidism but not hypothyroidism has a significant effect on weight

Abstract: Objective-Thyroid hormones are involved in metabolic regulation, but the degree to which they affect body weight and body mass index (BMI) in children is unclear. We examined the effect of hypo-and hyperthyroidism on weight and BMI at the time of diagnosis and after appropriate treatment. Design-Prospective and retrospective case seriesPatients-Children referred for thyroid dysfunction were enrolled prospectively if their total or free T4 was elevated with TSH <0.05 mIU/mL (N=57) or if they had a subnormal tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Eightyseven hyperthyroid patients had lost a mean of 16% of their body weights before hyperthyroidism at the time of presentation; 2 years following initiation of treatment, they had regained and slightly exceeded their baseline weight. A recent study of weight change following treatment of thyroid dysfunction in 57 hyperthyroid and 29 hypothyroid children similarly found that weight loss was minimal following treatment for hypothyroidism (mean 0.3 kg by the first follow-up visit) [5]. However, there was an average 7.1 kg gain in weight by the second follow-up visit following initiation of treatment for hyperthyroidism.…”
Section: Weight Change After Treatment For Thyroid Dysfunctionmentioning
confidence: 92%
“…Eightyseven hyperthyroid patients had lost a mean of 16% of their body weights before hyperthyroidism at the time of presentation; 2 years following initiation of treatment, they had regained and slightly exceeded their baseline weight. A recent study of weight change following treatment of thyroid dysfunction in 57 hyperthyroid and 29 hypothyroid children similarly found that weight loss was minimal following treatment for hypothyroidism (mean 0.3 kg by the first follow-up visit) [5]. However, there was an average 7.1 kg gain in weight by the second follow-up visit following initiation of treatment for hyperthyroidism.…”
Section: Weight Change After Treatment For Thyroid Dysfunctionmentioning
confidence: 92%
“…Information about weight gain during treatment of hyperthyroidism in children and adolescents is limited, and no studies identify predictors of weight gain in this population. In one study, patients predominantly receiving medical therapy had significant body mass index Z score (BMI‐Z) increases evident by 3 months after presentation that persisted throughout a 36‐month follow‐up period …”
Section: Introductionmentioning
confidence: 99%
“…Low thyroid hormone is associated with reduced energy expenditures (6) and fluid retention (7) in adults with overt hypothyroidism. However, less severe hypothyroidism does not appear to induce greater body fatness or weight, since l-thyroxine replacement leads to relatively small changes in body composition (8, 9). Elevated thyroid stimulating hormone (TSH) that does not exceed 2.5 times the upper limit of the normal range in association with a normal free thyroxine (FT4) concentration, referred to as “subclinical hypothyroidism,” is frequently observed in adults with obesity who have no evidence of autoimmune thyroiditis (10).…”
Section: Introductionmentioning
confidence: 99%